Adaptive synergetic MPPT controller for optimal performance of photovoltaic systems - Behih, Khalissa; Zerroug, Nadjat; Bouchama, Ziyad; Essounbouli, Najib; Benheniche, Abdelhak; Zebiri, Fouad (Archives of Control Sciences, 2026)
This paper presents a novel optimization strategy for photovoltaic (PV) power systems based on a synergetic control (SC) theory integrated with state observation and adaptive estimation schemes. The main objective is to enhance system reliability and reduce implementation costs through the elimination of selected physical sensors. A state observer is designed to ensure stable system operation and avoid control-law singularities, while adaptive laws are employed to accurately estimate the load and the photovoltaic output voltage. These estimated states are provided to the synergetic controller, which drives the system to operate at the maximum power point (MPP). The proposed strategy is validated through numerical simulations under dynamic conditions, including variations in solar irradiance, temperature, and load. Furthermore, experimental tests corroborate the simulation results, confirming the robustness and high efficiency under partial shading conditions and demonstrating the strategy's practicality for real-world PV systems.